Comparison of the linear mechanical deformation of the cushioning material of running shoes between different sizes of the same brand and model - Barbosa, Ana Clara Dvilla Gonçalves; Oliveira, Murilo Xavier; Bernardes, Fernanda Ribas; Pertence, Antônio Eustáquio de Melo; Brant, Alicia Corrêa; Gomes, Rosalina Tossige; Costa, Henrique Silveira; Magalhães, Fabrício Anicio; Trede Filho, Renato Guilherme Trede Filho (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
Running shoes were the first footwear to successfully incorporate cushioning technologies. The purpose of cushioning is to attenuate the ground reaction force after initial foot contact during running. The cushioning has been shown to provide benefits including the prevention of injury, and improvement in running performance; however, more information is needed in relation to changes in the density of the cushioning material in different shoe sizes. This study aimed to compare the deformation of cushioning under compression between different sizes of shoes from the same model and brand. Methods: This is a cross-sectional observational study evaluating eight new identical sports shoes, varying only in color and size (from 6US to 11US). The region of the cushioning of the shoes was submitted to compression through a hydraulic press, which exercised a varying load of 10 kg in increments of 10 kg until 100 kg was reached. The load was monitored by a digital dynamometer. The linear deformation of the cushion was recorded through a millimeter ruler attached to the system. MANOVA was performed using the statistical package SPSS version 18.0. It was considered the level of P < 0,05. Results: There was no statistically significant difference between the mean of linear displacement and the size of shoes for all strata of loads applied to the pads. Conclusion: The material used for the construction of sports shoes shock absorbers of the same brand and model analysed is not differentiated between the sizes, which could compromise their function.